Spontaneous gastrocutaneous fistula - Guicheff, Vladimir; Villagran, Raul; Favat, Juan; Ramoe, Sergio (Cirugía del Uruguay, 1974)
A case that we think presents a double interest is reported. On one hand, the presentation of a spontaneous gastrocutaneous fistula, an extremely rare case. On the other, the need of the clinic's severe watch, in the correction of any metabolic disturb, the lack of wich could carry fatal consequences to the patient's evolution.